A CONSTITUTIONAL-ETHICAL STUDY OF THE INDONESIAN CONSTITUTIONAL COURT DECISION NUMBER 62/PUU-XXII/2024 ON THE CONSTITUTIONALITY REVIEW OF THE PRESIDENTIAL THRESHOLD - Cyrilius W.T. Lamataro; Vergilius Septyanto Lamabelawa; Jenny Ermalinda; Chatryen Megawati Dju Bire; Adhe Ismail Ananda (PT. Radja Intercontinental Publishing, 2026)
The Indonesian Constitutional Court Decision Number 62/PUU-XXII/2024 was not the first attempt by petitioners to challenge the constitutionality of the presidential threshold. From 2004 to 2023, the Court had examined at least 46 cases concerning the presidential threshold, most of which were declared inadmissible, rejected, partially granted, or withdrawn by the petitioners. This raises an important question: what considerations led the Court to change its constitutional stance on the presidential threshold? This study aims to examine the ratio decidendi of Constitutional Court Decision Number 62/PUU-XXII/2024 and to analyze its ethical-constitutional dimensions. This research employs normative legal research methods using statutory, case, and conceptual approaches. The findings show, first, that the ratio decidendi of the decision rests on the protection of the constitutional rights of political parties participating in elections, the guarantee of citizens’ political rights to vote and to be elected, and the purification of presidentialism through the strengthening of the checks and balances system in Indonesia. Second, the Court reconstructed its constitutional reasoning on the presidential threshold by taking into account the moral principles embedded in the Constitution. Its considerations regarding the political rights of citizens and political parties, as well as the logical fallacies underlying the presidential threshold, indicate that eliminating the threshold may strengthen rather than weaken Indonesia’s presidential system.